Modeling the particle flux effect on distribution of (230)Th in the equatorial Pacific - Siddall, M; Anderson, R; Winckler, G; Henderson, G; Bradtmiller, L; McGee, D; Franzese, A; Stocker, T; Mueller, SA (2008)
The normalization of sediment accumulation rates by 230Th is increasingly used to constrain particle rain rates because 230Th is produced at a known rate in the water column and removed relatively quickly to the sediment. Several recent contributions have questioned this approach and suggested that the preferential removal of 230Th in areas of high particle flux, the "particle flux effect," introduces a systematic bias in the 230Th normalization technique. We use a circulation model that includes a description of particle scavenging to show that the particle flux effect cannot explain observations of high 230Th accumulation in equatorial Pacific sediments (relative to 230Th production in the water column). We further consider the possible variation of particle rain rates over time. We find only a minimal sensitivity in the particle flux effect due to increases in the particle rain rate at the equatorial Pacific by a factor of up to 10. This situation exists because the residence time of 230Th in the water column is too short to permit significant lateral transport with reasonable isopycnal mixing coefficients. We conclude that the increased rates of 230Th accumulation found in equatorial Pacific sediments deposited during the Last Glacial Maximum cannot have been caused by the particle flux effect. Copyright 2008 by the American Geophysical Union.